Succession of Plant Spesies Following a Forest Fire on Mount Talang, West Sumatera - Sumbari, Chika; Dwipa, Aswaldi Anwar Indra (International Journal of Environment, Agriculture and Biotechnology, 2019)
This research was conducted from May to July 2018. Observation of vegetation was carried out in the ex-fire of Talang Mount area, while identification of vegetation was carried out in the Herbarium Biology Departmen, Faculty of Science and Mathematics Andalas University. The purpose of this study is to identify vegetation that grows after forest fire, to determine the effect of forest fire on the succession processes. Vegetation analysis in natural forest and post-combustion forest was carried out by making observation plots of vegetation with map sizes for seedling level of 2mx2m, sapling level of 5mx5m, pole level of 10mx10m and tree level with a size of 20mx20m. Observation data is carried out with important value index analysis, There are 22 identified vegetations that grow after forest fire. The influence of forest fire on the existence of the succession process indicated by the presence of plants that grow in the post-burning forest area, namely Similac sp and A6 plants.